PENGARUH ANTARA KEMAMPUAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KEPALA SEKOLAH SD SE KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Junaidi Abdullah; Isjoni; David Chairilsyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
There are still principals, either in public or private schools, who have different educational backgrounds, not only in teacher education but also in the non-educational field. Even the longer they serve as principals, it will create boredom without any mutations so it influences the principal’s performance. The research purpose of this article was to determine the effect of workability and work motivation on the principal’s performance of the elementary school in Bangko Pusako District, Rokan Hilir. The research used a survey method with a correlation technique. The research population involved 137 elementary school teachers in Bangko Pusako Subdistrict, Rokan Hilir. The sample was 101 teachers. Data from the research were collected by using a questionnaire technique. The research outcome showed that there was a positive and significant effect of workability on the principal’s performance of the elementary school in Bangko Pusako District, Rokan Hilir.